THE IMPACT ON FIRM PERFORMANCE : EVIDENCE FROM CEO EDUCATION - Silvina Silvina; Robin Robin; Wisnu Yuwono (Universitas Internasional Batam, 2022)
The purpose of this paper is to examine the impact of CEO Education on Firm Performance. The sample covers 180 observations from IDX LQ45 listed on the Indonesia Stock Exchange during the period 2017-2020. The CEO Education is defined by the field of study in Business, Economic and Management. Firm Performance is measured by Market based perspective. Board Characteristics and Stock Returns as control variables. The result shows that there’s a relationship between CEO Education and Firm Performance. CEO with Business, Economic and Management Background has a positive and significant impacts on Firm Performance. The result becomes stronger with additional test of the level and quality of CEO Education on Firm performance, supporting that CEO Education does enchance the Firm Performance.